Analisis Uji Kinerja Mesin Pencetak Briket Serbuk Kayu Gargajian dengan Sistem Pneumatik - Munawwaroh, Dita Anies; Sriyanto, Nanang Budi; Hidayat, Arif; Baskara, Danang Adi (Journal of Mechanical Engineering and Applied Technology, 2023)
Sawdust briquettes molding machine is a machine for printing sawn briquettes as an alternative replacement for fossil fuels. The filling and compacting sawdust briquettes sawn using a pneumatic system that aims to improve the productivity of printing sawdust briquettes sawn still manually. With the printing press sawdust briquettes sawn with pneumatic system is expected to get a working process faster and lower error and operator convenience in the work process. The method is performed in the manufacture of printing machines sawdust briquettes sawn with pneumatic system is to conduct election observation in the form of alternative designs, design, manufacturing, assembly up until the testing process and data retrieval. Results of design scorer sawdust briquettes sawn with a pneumatic system using 8 bar working pressure that is with dimensions of 100 mm x 150 mm x 70 mm. Results from the manufacture of machinery sawdust briquettes sawn printer with a pneumatic system can be deduced briquette machine can print with a capacity of 600 briquettes per hour with a good and efficient time.